Physicochemical and physiological changes during the ripening of banana (musaceae) fruit grown in Colombia - Moreno Alzate, Jhon Larry; Tran, Thierry; Cantero‐Tubilla, Borja; López López, Karina; Becerra López Lavelle, Luis Augusto; Dufour, Dominique (Wiley, 2021)
The physicochemical and physiological attributes of three contrasting commercial varieties of Musaceae: Dominico Harton (plantain), Guineo (cooking banana), and Gros Michel (dessert banana), were evaluated and statistically analyzed during postharvest ripening. Quality attributes differed markedly among varieties, both in fresh fruits and during ripening. Variety (V) had a significant effect (p<0.001) on all attributes except total soluble solids (TSS), carotenes and total chlorophyll. Storage time (ST) had a significant effect on all attributes except color parameter b* and total carotenes. Starch levels decreased significantly (p<0.001) during ripening, with nearly complete hydrolysis in Gros Michel, followed by Guineo and Dominico Harton. Discriminant analysis showed that central diameter, TSS of the pulp, color parameter a* and total starch had the highest weight in the differentiation among varieties. These results point out which parameters may help improve current methods for monitoring ripening of bananas, in particular the commercially important varieties in this study.